Design of atomic clock cavity based on a loop-gap geometry and modified boundary conditions. Issue 7 (27th June 2017) - Ivanov, Anton E.; Affolderbach, Christoph; Mileti, Gaetano; Skrivervik, Anja K.
Abstract : In this study, we investigate a concept that can be used to improve the magnetic field homogeneity in a microwave cavity applied in a novel, high-performance atomic frequency standard. We show that by modifying the boundary conditions in the case of a loop-gap geometry, a good improvement of the field homogeneity can be obtained. Such a design demonstrates high potential to improve the frequency stability; it is compact and hence suitable for a future generation of compact, high-precision frequency standards based on vapor cells and a pulsed optical pumping (POP) regime (POP atomic clocks).